Justification of Intimate Partner Violence among Women of Reproductive Age in Nigeria: Analysis of 2011-2021 Multiple Indicator Cluster Surveys - Olaniyi Felix Sanni; Abike Elizabeth Sanni; Tukwasi Ahamuefula; Oluwadare Peter Akeju; Collins Isioma onyeagwaibe (Journal of Epidemiology and Public Health, 2025)
Background: Women around the world face Intimate Partner Violence (IPV) as one of the most widespread forms of abuse, making it a serious public health issue globally. This study seeks to analyse multi-year trends in the justification of intimate partner violence in Nigeria and identify key influencing factors.Subjects and Method: This cross-sectional study used data from the 2011, 2016/17, and 2021 Nigeria MICS, targeting women aged 15–49 across the country. A stratified two-stage sampling design ensured national representation. Justification of intimate partner violence was the main outcome, analysed using binomial logistic regression. Crude and adjusted odds ratios were estimated, with significance set at p < 0.050.Results: The prevalence of IPV justification was 37.2%. The trend peaked in 2011 at 37.3%, a decrease to 30.1% in 2016/17, and a rise to 32.6% in 2021. Factors associated with higher odds of IPV justification include women aged 25 to 34 (AOR= 0.96) and 44 to 49 (AOR= 0.85), non-formal education (AOR= 1.69), primary education (AOR= 1.84), and secondary education (AOR= 1.641). Additionally, living in rural areas (AOR= 1.278), being pregnant (AOR= 1.11), having a husband or partner with multiple spouses (AOR= 1.25), and belonging to the poorest (AOR= 1.92), middle (AOR= 1.63), or fourth (AOR= 1.48) wealth quintiles are linked to an increased likelihood of justifying IPVt.Conclusion: This study’s findings can assist the government and relevant organizations in designing strategies to reduce IPV justification by introducing proper education, poverty alleviation programs, and enlightening campaigns.